PENDIDIKAN SEKS DALAM KELUARGA DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Melya Irawati; T. Romi Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in Simpang Baru Urban Village,, Tampan Subdistrict, Pekanbaru City, with the aim of knowing parents' understanding of sex education and knowing how the application of sex education by parents in the Simpang Baru Subdistrict, Tampan District, Pekanbaru to children to prevent sexual harassment and crime in the city. Pekanbaru. This research is a quantitative descriptive study. The population in this study amounted to 1201 people, by counting samples using Slovin formula so that the number of samples obtained in this study were 92 respondents. The researcher used the Cluster Random Sampling method to determine the location of the sample and the determination of the sample was done by Snowball Sampling. To collect data, researchers used data collection of observational information, documentation, and interviews with questionnaires as interview tools. To analyze the research data, quantitative analysis was used and described descriptively. Based on the research that has been done, it can be concluded that of the 92 respondents in this study 70 of them had high levels of knowledge about sex education, which means that the majority of respondents already knew sex education well. And for the application of sex education from 92 respondents in this study 80 respondents among them had a high level of sex implementation. This proves that most respondents are aware of the importance of sex education and have applied this to children well Keywords: sex education, family